Prophylactic Hypogastric Artery Ligation during Placenta Percreta Surgery: A Retrospective Cohort Study - Kuhn, Theresa; Martimucci, Kristina; Al-Khan, Abdulla; Bilinski, Robyn; Zamudio, Stacy; Alvarez-Perez, Jesus (American Journal of Perinatology Reports, 2018)
Objective To evaluate if prophylactic hypogastric artery ligation (HAL) decreases surgical blood loss and blood products transfused.Study Design This is a retrospective cohort study comparing patients with placenta percreta undergoing prophylactic HAL at the time of cesarean hysterectomy versus those who did not. Data were presented as means ± standard deviations, proportions, or medians with interquartile ranges. Demographic and clinical data were compared in the groups using Student's t-test for normally distributed data or the Mann–Whitney U test for nonnormally distributed data. Fisher's exact test was used for proportions and categorical variables. Data are reported as significant where p was <0.05.Results There were 26 patients included in the control group with no HAL and 11 patients included in the study group. Estimated blood loss for the study group was 1,000 mL versus 800 mL in the control. Units of PRCBs transfused were 4.5 units in the study group versus 2 units for the control group. None of these measures were found to be statistically significant.Conclusion Our data suggest there was no benefit in the use of prophylactic HAL in decreasing surgical blood loss or amount of blood products transfused in patients who had a cesarean hysterectomy performed for placenta percreta.Précis Prophylactic HAL does not decrease blood loss during surgery for placenta percreta.
Keywords: abnormally invasive placentation; placenta percreta; cesarean hysterectomy; hemorrhage; hypogastric artery ligation